Psychological Capital of Entrepreneur Teams and Human Resource Development - Tang, Jun-Jun (Frontiers in Psychology, 2020)
The ability of an organization to materialize its objectives largely depends on the psychological and physical participation of the employees and staff members. The theory of psychological capital focuses on how an individual is changing or evolving, rather than who that individual is. Thus, the concept of PsyCap should be tightly tied and discussed with human resource development (HRD), both from practical and theoretical lens. This paper sets to discuss the strategic and entrepreneurial associations between PsyCap and HRD. The goal is to shed light on potential practical designs and theoretical improvement in the future.